Comparison of the Ileal Digestibility of Amino Acids in Meat and Bone Meal for Broiler Chickens and Growing Rats - Ravindran, V.; Hendriks, W.H.; Thomas, D.V.; Morel, P.C.H.; Butts, C.A. (International Journal of Poultry Science, 2005)
The apparent ileal amino acid digestibility in 15 meat and bone samples was compared in growing broiler chickens and growing laboratory rat. The animals were given a diet containing meat and bone meal as the sole source of protein. All diets contained chromic oxide as the indigestible marker to calculate the digestibility estimates. Comparison of digestibility data shows that, for all dispensable amino acids, apparent ileal amino acid digestibility was similar (p>0.05) between broiler chicken and the growing rat. However, the ileal amino acid digestibility was similar (p>0.05) between the two species for only four (histidine, methionine, threonine and valine) of the nine indispensable amino acids. Significant differences (p